Complete active space analysis of a reaction pathway: Investigation of the oxygen–oxygen bond formation. Issue 17 (14th April 2020) - Han, Ruocheng; Luber, Sandra
Abstract: Water nucleophilic attack is an important step in water oxidation reactions, which have been widely studied using density functional theory (DFT). Nevertheless, a single‐determinant DFT picture may be insufficient for a deeper insight into the process, in particular during the oxygen–oxygen bond formation. In this work, we use complete active space self‐consistent field calculations and describe an approach for a complete active space analysis along a reaction pathway. This is applied to the water nucleophilic attack at a Ru ‐based catalyst, which has successfully been used for efficient water oxidation and in silico design of new water oxidation catalysts recently. Abstract : The water nucleophilic attack at a Ru ‐based water oxidation catalyst is investigated in detail based on an approach for complete active space calculations along the entire reaction pathway.